2016
DOI: 10.18632/oncotarget.7101
|View full text |Cite
|
Sign up to set email alerts
|

Blastic plasmacytoid dendritic cell neoplasm frequently shows occult central nervous system involvement at diagnosis and benefits from intrathecal therapy

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare aggressive myeloid neoplasm which shows a high rate of central nervous system (CNS) recurrence and overall survival (OS) of <1 year. Despite this, screening for CNS involvement is not routinely performed at diagnosis and intrathecal (IT) prophylaxis is not regularly administered in BPDCN. Here, we prospectively evaluated 13 consecutive BPDCN patients for the presence of CNS involvement by flow cytometry. Despite none of the patients presented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 21 publications
0
50
1
Order By: Relevance
“…Larger prospective studies will be required to address the relationship, if any, between NR3C1 haploinsufficiency, residual disease, and the presence of central nervous system involvement at diagnosis which has been implicated in rapid disease recurrence in BPDCN patients. 56 As proposed recently, 55 restoring normal GCR levels from the intact NR3C1 allele might represent a route to overcoming glucocorticoid-based therapy failure in NR3C1-haploinsufficient BPDCN. Of note in this context is the finding that thalidomide appears to specifically benefit patients presenting with multiple myeloma and low GCR expression.…”
Section: Discussionmentioning
confidence: 96%
“…Larger prospective studies will be required to address the relationship, if any, between NR3C1 haploinsufficiency, residual disease, and the presence of central nervous system involvement at diagnosis which has been implicated in rapid disease recurrence in BPDCN patients. 56 As proposed recently, 55 restoring normal GCR levels from the intact NR3C1 allele might represent a route to overcoming glucocorticoid-based therapy failure in NR3C1-haploinsufficient BPDCN. Of note in this context is the finding that thalidomide appears to specifically benefit patients presenting with multiple myeloma and low GCR expression.…”
Section: Discussionmentioning
confidence: 96%
“…The CNS may represent a blast cell sanctuary in BPDCN patients with leukemic presentation both at diagnosis and at relapse. 4 Efforts are currently being made to generate new synthetic agonists with increased specificity for the LXRb isoform, expressed by BPDCNs, to limit steatosis 19,49 and/or to stimulate LXR specifically in a target tissue. 50,51 Our study supports a new approach for BPDCN treatment using these new synthetic LXR agonists.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 It has been recently proposed that the frequent relapse after treatment and the poor prognosis can be related to the fact that the involvement of the central nervous system (CNS) is frequently undetected. 4 Recently, BPDCN was classified by the World Health Organization (WHO) as a distinct entity in the group of "acute myeloid leukemia (AML) and related precursor neoplasms." 2,5 Extensive characterization of this malignancy is still limited and diagnosis overlap may exist with immature AML, monoblastic and undifferentiated leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recent literature brought attention to the high percentage of primary CNS involvement (10%) at diagnosis or during relapse of disease (30%) observed in BPDCN, suggesting that the CNS is a sanctuary for cells in patients with primary leukemic presentation and perhaps all BPDCN, given the high incidence encountered in relapse. 31,46 In support of this concept, patients treated with ALL-type regimens, which include aggressive CNS prophylaxis followed by allo-SCT, seem to do better. Upon validation with an additional retrospective cohort of 23 patients, Martín-Martín et al 46 demonstrated that patients receiving prophylactic intrathecal therapy (5 of 23) had both prolonged CNS recurrence-free disease and OS.…”
Section: Relapsed or Refractory Diseasementioning
confidence: 99%